Promoting self-regulated learning in preschoolers - Lisa Jacob; Manuela Benick; Sandra Dörrenbächer; Franziska Perels (Journal of Childhood, Education & Society, 2020)
Self-regulated learning (SRL) is important for a person's school career and their later academic success, and it should therefore be fostered as early as possible. Nevertheless, research focusing on the promotion of SRL in preschoolers is limited. The present study aims to examine the efficacy of an SRL intervention based on a longitudinal control-group-design for preschoolers (direct-level intervention) and their kindergarten teachers (indirect-level intervention). The SRL intervention took place in either a) an autonomous learning environment, where SRL learning strategies were practiced with no special focus on the stimulation of communicative abilities or b) in a social-interactive learning environment, where SRL learning strategies were practiced while communicative abilities were stimulated. The sample consisted of 189 preschoolers (49.5% ♀, 50.5% ♂, mean age: 5.6 years, SD = .47 years) and 30 kindergarten teachers. SRL and general self-regulation ability (gSR) served as performance measures. The results of the paired t-tests revealed an increase in SRL and gSR for preschoolers irrespective of the condition, while a group-differential intervention benefit for preschoolers (i.e. direct-autonomous or direct-interactive intervention) could not be confirmed by the applied repeated measures ANOVA and contrast analyses. Further, we did not find any substantial benefit from teacher intervention (i.e. indirect intervention) analysed by non-parametric Wilcoxon test. This unexpected result is discussed in light of methodical considerations. Nevertheless, the study provides important implications for future intervention studies.